Effects of childcare disagreement with children, social support, and health status on unmet healthcare-seeking behavior among the migrant older with children to Jinan, China - Shi, Xinfei; Zong, Di; Lu, Zhongqian; Li, Shixue; Kong, Fanlei (Frontiers in Public Health, 2022)
Due to the acceleration of China's urbanization, the number of migrant older with children (MOC) continued to increase. This study aimed to clarify the effects of childcare disagreement with children, social support, and health status on unmet healthcare-seeking behavior among the MOC to Jinan, China. A cross-sectional study included 656 MOC (36.3% men and 63.7% women) using multi-stage cluster random sampling in Jinan, China. Childcare disagreement was evaluated by the differences between parents and grandparents on the diet, dressing, education, and childcare consumption. Social support was assessed using the social support rating scale (SSRS). Descriptive analysis, chi-squared test, and binary logistic regression were applied to analyze the association between childcare disagreement with children, social support, health status, and unmet healthcare-seeking behavior of the MOC. Approximately 41.3% of participants had unmet healthcare-seeking behavior. Logistic regression analysis showed that the MOC whose health status compared to last year get better were more likely to have unmet healthcare-seeking behavior, while who were women, had partial will of migration, hired a nanny, had smaller childcare disagreement with children on dressing, had smaller childcare disagreement with children on consumption, and had moderate social support, were less likely to experience unmet healthcare-seeking behavior. Recommendations were given to the government and family members to improve the health services-seeking behavior of the MOC.